2003
DOI: 10.1159/000071700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress and Adrenalectomy on Urocortin II mRNA Expression in the Hypothalamic Paraventricular Nucleus of the Rat

Abstract: Urocortin II (Ucn II) is a novel corticotropin-releasing hormone (CRH)-related peptide discovered as a selective agonist for type-2 CRH receptor. In the rat or mouse brain, Ucn II mRNA shows weak expression mainly in the hypothalamic paraventricular nucleus (PVN) and the locus coeruleus (LC). Understanding the regulation of Ucn II mRNA expression under varying conditions provides new insights into central stress response. We examined expression of Ucn II mRNA in the PVN and LC following immobilization stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
(60 reference statements)
3
26
3
Order By: Relevance
“…Rodents normally exhibit proportionally more drinking during nocturnal than diurnal phases in relation to osmotic challenges, such as feeding (Johnson and Johnson, 1990a,b;Johnson et al, 2003;Zorrilla et al, 2005). As noted above, the colocalization of Ucn-2 and AVP in the magnocellular neurons of the PVN, its regulation by water deprivation (Tanaka et al, 2003), and the increase expression of AVP in the PVN and SON nuclei of the female Ucn-2-deficient mice may suggest a possible role for Ucn-2 in modulating fluid intake under specific osmotic challenges. Because CRFR2 is expressed in the PVN, Ucn-2 may regulate AVP expression or secretion in an autocrine or/and paracrine manner in the magnocellular PVN.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Rodents normally exhibit proportionally more drinking during nocturnal than diurnal phases in relation to osmotic challenges, such as feeding (Johnson and Johnson, 1990a,b;Johnson et al, 2003;Zorrilla et al, 2005). As noted above, the colocalization of Ucn-2 and AVP in the magnocellular neurons of the PVN, its regulation by water deprivation (Tanaka et al, 2003), and the increase expression of AVP in the PVN and SON nuclei of the female Ucn-2-deficient mice may suggest a possible role for Ucn-2 in modulating fluid intake under specific osmotic challenges. Because CRFR2 is expressed in the PVN, Ucn-2 may regulate AVP expression or secretion in an autocrine or/and paracrine manner in the magnocellular PVN.…”
Section: Discussionmentioning
confidence: 97%
“…Ucn-2 is expressed by several hypothalamic nuclei, with highest levels of expression in the magnocellular neurons of the PVN . A recent study demonstrated a strong induction of Ucn-2 mRNA expression in the parvocellular region of the PVN after immobilization stress and dramatic Ucn-2 mRNA expression in the magnocellular division of the PVN after water deprivation (Tanaka et al, 2003). Using doublelabel in situ hybridization, Tanaka et al showed that Ucn-2 is colocalized with ϳ45% of CRF-expressing cells in the parvocellular part of the PVN and with most of the AVP neurons in the magnocellular part of the PVN after immobilization and water deprivation paradigms, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Others and we previously demonstrated that Ucn2 is expressed in both the brain and peripheral tissues, including the lung, adrenal, uterus, ovary, and testis (Hsu & Hsueh 2001, Yamauchi et al 2005, Lee et al 2011. It has been reported that expression of Ucn2 mRNA in various tissues is controlled by stress, inflammation, and hypoxia (Tanaka et al 2003, Tao et al 2006, Chang et al 2007, Buhler et al 2009, Imperatore et al 2010, Nemoto et al 2010 and that factors involved in the regulation of Ucn2 mRNA expression are CRF, glucocorticoids, and endotoxins (Chen et al 2003(Chen et al , 2004mechanisms of Ucn2 expression in reproductive organs are not well understood.…”
Section: Introductionmentioning
confidence: 95%